Aspek Pemasaran dalam Kelayakan Usaha untuk Meningkatkan Kunjungan Konsumen di Kafe “Itangi” - Caroline Winona; Eva Handayani; Hanny Putri Fathiya; Yohanna Angelina Samar; Budi Setiawan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Purpose: With time, competition in business is getting fiercer. Failure and loss have become common risks. By studying business feasibility, one aspect of which is marketing, losses can be minimized. This title was chosen because it is important for business people to develop a marketing strategy that is suitable for the intended market so that business sustainability is maintained. Marketing is crucial in business, because without effective marketing, potential customers will not know about our business, so they cannot become our customers. This research aims to study general consumer preferences and relevant marketing strategies. Methods: Using a descriptive qualitative method the author conducted in-depth interviews with open-ended questions, conducted with 10 respondents. Implication: A cozy atmosphere, innovative menu, and competitive prices are the main elements that consumers look for in a cafe. Marketing strategies through social media with creative content and attractive promotions will be very effective to increase the appeal of iTangi.